Calculation of Annual Energy Requirement of Existing Constructions and Improvement Suggestions for Building Envelope: An Educational Structure Example - Arslan Beytekin, Hatice Elif; Sezer, Filiz Senkal (European Journal of Sustainable Development, 2017)
The energy problem is becoming increasingly important all over the world due to its environmental and economic dimensions. Due to their high energy needs, buildings have a significant share in total energy consumption. For this reason, the design of environmentally friendly structures that use energy efficiently or the conversion of existing structures into energy efficient structures has become a priority in the policies of many countries today. In this study, using the Design Builder program, one of the international energy simulation programs that measure energy efficiency, the total annual energy requirement of an existing building selected as an example to be taken into consideration for the current application project, has been calculated. In addition, the building is divided into, and the energy needs are calculated separately for heating, cooling, electrical equipment and lighting by zone. Two different suggestions have been presented for the improvement of the building envelope in line with these results. One of the proposals was made by taking into consideration the TS 825 Thermal Insulation Regulation, valid in Turkey. In the 2nd suggestion, a general approach was taken, determining the zones where the energy needs are highest per unit area, and a building envelope suggestion providing the balancing of the energy needs for these zones to the general needs of the building has been developed. Keywords: Energy efficiency, building envelope, design builder